2015
DOI: 10.1177/107327481502200212
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Vascular Endothelial Growth Factor A in Invasive Micropapillary Colorectal Carcinoma

Abstract: The strong coexpression of VEGF-A and CD31 suggests a prominent role of neoangiogenesis in these tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…VEGF-C and VEGF-D are important in the process of lymphangiogenesis, while VEGF-A, VEGF-B and placental growth factor are important in neovascularization[163-166]. The most potent pro-angiogenic growth factor, VEGF-A binds to its receptors VEGFR-1 and VEGFR-2 and thereby increases endothelial cell survival, proliferation, migration and differentiation[167,168].…”
Section: Pathophysiology Of Colorectal Pcmentioning
confidence: 99%
“…VEGF-C and VEGF-D are important in the process of lymphangiogenesis, while VEGF-A, VEGF-B and placental growth factor are important in neovascularization[163-166]. The most potent pro-angiogenic growth factor, VEGF-A binds to its receptors VEGFR-1 and VEGFR-2 and thereby increases endothelial cell survival, proliferation, migration and differentiation[167,168].…”
Section: Pathophysiology Of Colorectal Pcmentioning
confidence: 99%
“…Angiogenesis is central to the growth and metastasis of cancers; and VEGF is the key driver of tumor neovascularization, progression, and malignant phenotype [ 29 , 45 ]. Additionally, cluster of differentiation 31 (CD31) also plays a complex role in tumor angiogenesis [ 46 ]. These observations provide a strong reason for the importance of VEGF and CD31 as a potential targets in modern cancer therapy by developing strategies that can inhibit VEGF and/or to disrupt its signaling pathway [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, cluster of differentiation 31 (CD31) also plays a complex role in tumor angiogenesis [ 46 ]. These observations provide a strong reason for the importance of VEGF and CD31 as a potential targets in modern cancer therapy by developing strategies that can inhibit VEGF and/or to disrupt its signaling pathway [ 45 , 46 ]. Herein, our findings were in harmony and elucidated that Ad-ΔB/TRAIL and Ad-ΔB/IL-12 combination treatment was associated with a clear reduction in the intratumor expression of VEGF, CD31-positive cells, and in the microvessel density than the effects mediated by Ad-ΔB alone; suggesting a co-operative interaction between the administered OAds and their delivered TRAIL and IL-12 genes in halting tumor-driven angiogenesis and neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…3). It was previously reported that VEGF-A was overexpressed in invasive micropapillary colorectal carcinoma [16]. This might contribute to a response to bevacizumab, which is a monoclonal antibody against VEGA-A.…”
Section: Discussionmentioning
confidence: 99%